Children in Exile: Recollections of Childhood in the Soviet Gulag - Swider, Chris (United States : Opus 27 Productions ; Bulletproof Film, 2007)
In Children in Exile survivors of Soviet deportation to Siberia describe their experiences as the youngest victims of the massive crimes against humanity perpetrated by the Soviet system. It is a documentary about the youngest victims of the repressions carried out by the Soviet Union during the Second World War, the children and teenagers deported to Soviet Siberia and Kazakhstan. These abuses, part of a larger campaign of ethnic cleansing, have never been confronted. No one was put on trial, and no reparations have ever been paid. Americans need to know about these crimes against humanity because their shadow lingers over current events. Joseph Stalin infamously said that one death is a tragedy, but a million deaths are a statistic. The Soviet Secret Police deported millions, and somehow the world remains indifferent. Children in Exile hopes to challenge this indifference by filling in the human face to this terrible statistic and monumental tragedy.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films